2019
DOI: 10.1212/wnl.0000000000007174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blood pressure and lipid lowering on cognition

Abstract: ObjectiveTo assess whether long-term treatment with candesartan/hydrochlorothiazide, rosuvastatin, or their combination can slow cognitive decline in older people at intermediate cardiovascular risk.MethodsThe Heart Outcomes Prevention Evaluation-3 (HOPE-3) study was a double-blind, randomized, placebo-controlled clinical trial using a 2 × 2 factorial design. Participants without known cardiovascular disease or need for treatment were randomized to candesartan (16 mg) plus hydrochlorothiazide (12.5 mg) or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…[18][19][20] However, post hoc analysis from the HOPE-3 study found no significant deterioration in neurocognitive function with rosuvastatin treatment, as assessed by MoCA and TMT. 37 A meta-analysis by Ott et al 38 did not find a significant difference in the incidence of dementia, confusion, or other adverse cognitive events between the statin and placebo groups among patients with normal cognition at baseline. Moreover, a crosssectional study in coronary artery disease patients found high-dose statin to be associated with better cognition than low-dose statin, as assessed by MoCA and TMT.…”
Section: Discussionmentioning
confidence: 97%
“…[18][19][20] However, post hoc analysis from the HOPE-3 study found no significant deterioration in neurocognitive function with rosuvastatin treatment, as assessed by MoCA and TMT. 37 A meta-analysis by Ott et al 38 did not find a significant difference in the incidence of dementia, confusion, or other adverse cognitive events between the statin and placebo groups among patients with normal cognition at baseline. Moreover, a crosssectional study in coronary artery disease patients found high-dose statin to be associated with better cognition than low-dose statin, as assessed by MoCA and TMT.…”
Section: Discussionmentioning
confidence: 97%
“…However, most investigations have assessed the presence of vascular risk factors or risk factor modification and related these to global cognition, using either MMSE or composite cognitive scores 15 – 19 . One recent study has reported a benefit of statin and BP-lowering medication using a more sensitive digit-symbol substitution score in healthy people without any known cardiovascular disease 20 . Overall, however, to the best of our knowledge there has been no clear demonstration of a parametric effect of risk factors (e.g., BP level, rather than simply presence or absence of hypertension or BP-lowering treatment) associated with systematic differences in cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…The ACC/AHA reviewed statin safety data and addressed it in the 2013 cholesterol guideline and showed no randomized controlled trial evidence of statin‐associated cognitive change or risk of dementia . Recent data from the HOPE‐3 randomized controlled trial in a population with a mean age 74 years showed that candesartan with hydrochlorothiazide, rosuvastatin, or their combination did not significantly affect cognitive decline in this study of older adults . Additionally, autopsy studies show no significant difference in Alzheimer's disease onset or in burden of plaques and tangles on autopsy study in those on a statin, compared with those not on statin therapy …”
Section: Case Studymentioning
confidence: 54%
“…42 Recent data from the HOPE-3 randomized controlled trial in a population with a mean age 74 years showed that candesartan with hydrochlorothiazide, rosuvastatin, or their combination did not significantly affect cognitive decline in this study of older adults. 43 Additionally, autopsy studies show no significant difference in Alzheimer's disease onset or in burden of plaques and tangles on autopsy study in those on a statin, compared with those not on statin therapy. 44,45 A CAC score could be performed in the case of B.H., just as it was in case 1.…”
Section: Case Studymentioning
confidence: 98%